Statistical Discrimination and Optimal Mismatch in College Major Selection - Mary Kate Batistich; Timothy N. Bond; Sebastian Linde; Kevin J. Mumford (Institute of Labor Economics (IZA), 2024)
We develop a model of college major selection in an environment where firms and students have incomplete information about the student's aptitude. Students must choose from a continuum of majors which differ in their human capital production function and can act as a signal to the market. Whether black students choose more or less difficult majors than similar white students, and whether they receive a higher or lower return to major difficulty, depends on the extent to which employers statistically discriminate. We find strong evidence that statistical discrimination influences major choice using administrative data from several large universities and two nationally representative surveys.
Keywords: J71; J15; I26; 330; mismatch; affirmative action; statistical discrimination